From the Dynamic Demagnitizing Factor to the Heat Capacity of a Nanodispersed Magnetic Fluid - S.G. Emelyanov; V.M. Polunin; A.O. Tantsyura; A.M. Storozhenko; P.A. Ryapolov (Журнал нано- та електронної фізики)
A technique for the measurement of the dynamic demagnetizing factor, used for the description of magnetic fluid magnetization disturbance caused by a sonic wave has been offered. The formula for the calculation of heat capacity Cp of the synthesized magnetic colloids, which includes the pa-rameter Nd has been obtained.